The Viewpoints: Determination of Elementary School Teacher’s Preference and Criteria for Selecting Children’s Books - Alamsyah, Zulfikar; Damaianti, Vismaia S.; Sunendar, Dadang (Universitas Pendidikan Ganesha, 2024)
The issue of reading literacy is a frequently discussed topic in the Indonesian education system. However, the main problem does not lie in the literacy activities themselves but rather in the reading materials provided for children. This research aims to analyze how elementary school teachers choose reading materials for their students. It utilizes a qualitative method with a case study approach. Data collection involves observation, interviews, and documentation in four different elementary schools. The primary sources of this research are the interviews and observations conducted with teachers of upper-grade classes (grades 4, 5, and 6). An interesting finding in this research is that elementary school teachers select children's literature based on literary elements and its relevance to the Indonesian language teaching materials. For a more comprehensive explanation, this aspect is further discussed in the article. In conclusion, elementary school teachers choose reading materials based on the intrinsic elements of the work, and there is no comprehensive assessment in the selection process.